A special doping regime in silicon wafer nanocolumns - Tarnavsky, G.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2010)
Computer simulation for the ion implantation of impurities into silicon plate surface nanocolumns is conducted when the ion stream line is parallel to the plate base.